Analysis of the Impact of Worker Age on Behavioral Differences Occupational Safety and Health in Construction Ploso Jombang Bridge - Moch Nahar Sholahuddin; Farida Hardiningrum (NAROTAMA UNIVERSITY, Indonesia, 2022)
The construction of the Ploso Bridge intends to connect access traffic road between Jombang on the north side and Jombang on the south side. The construction of the Ploso Jombang Bridge project, as in the construction of the bridges in general which give rise to various unintended consequences desire, among others, regarding aspects of occupational health and safety, occupational diseases and occupational diseases. This research has the aim of find out how much influence the age of workers has on behavior differences in health and work safety in the construction of the Ploso Bridge Jombang who has practiced the K3 system. The aims of this research are, 1) To recognize the impact of worker age on safety behaviour. 2) Use recognize the link between work experience and safety behaviour. 3) To identify the education level of workers with safety behavior. Collecting data in this research using questionnaires to the participants workers which include craftsmen and coolies, as many as 50 samples. based on because often work accidents in the field occur to craftsmen and coolies spearheading a construction project due to a work accident, with. After the results of the questionnaire have been filled in all then inputted into excel by making noun data. After that, the results can be compared workers for ages 17-30 years with workers 30-55 years old to measure there is a difference in safety behavior or not, by using tests predetermined test, In this analysis of the impact of worker age using Validity Test technique, Reality Test, Normality Test, Crosstab Test, F and Z . TEST